2012
DOI: 10.1155/2012/836519
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Exercise and Metabolic Disorders on Heat Shock Proteins and Vascular Inflammation

Abstract: Heat shock proteins (Hsp) play critical roles in the body's self-defense under a variety of stresses, including heat shock, oxidative stress, radiation, and wounds, through the regulation of folding and functions of relevant cellular proteins. Exercise increases the levels of Hsp through elevated temperature, hormones, calcium fluxes, reactive oxygen species (ROS), or mechanical deformation of tissues. Isotonic contractions and endurance- type activities tend to increase Hsp60 and Hsp70. Eccentric muscle contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 176 publications
(206 reference statements)
4
31
0
Order By: Relevance
“…Previous studies reported that obesity and insulin resistance are associated with impaired expression of various components of the heat shock response, including members of DNAJ family [6,65,66]. It is also known that physical exercise induces the heat shock response and improves the clinical parameters associated with obesity and insulin resistance [13,67]. In our current investigation, we also showed that exercise induced the expression of HDAC4.…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies reported that obesity and insulin resistance are associated with impaired expression of various components of the heat shock response, including members of DNAJ family [6,65,66]. It is also known that physical exercise induces the heat shock response and improves the clinical parameters associated with obesity and insulin resistance [13,67]. In our current investigation, we also showed that exercise induced the expression of HDAC4.…”
Section: Discussionsupporting
confidence: 76%
“…Exercise is also associated with transient elevations of Hsp expression, which may reduce inflammatory mediators (Noble and Shen 2012), suggesting that these proteins act as mediators of the effects of exercise on the immune function (Walsh et al 2001). Hsp70 is one of many DAMPs recognized by both TLR2 and TLR4 (Asea et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This was associated with decreases in Hsp70 levels in the FHL in response to exercise in both healthy and diabetic rats that were not observed in the soleus, which was not targeted by this training protocol. The process of muscle hypertrophy has been suggested to be preceded by muscle-damaging stress (Bischoff and Heintz 1994), indicating that an acute exercise overload may be considered stressful and may initiate the stress responses and production of inflammatory mediators (Malm 2001;Noble and Shen 2012;Silver et al 2012). However, some studies have shown that exercise training adaptations instead decreased inflammatory mediators and stress factors in skeletal muscle (Atalay et al 2004;Calle and Fernandez 2010;Molanouri Shamsi et al 2014).…”
Section: Discussionmentioning
confidence: 99%